2011
DOI: 10.1099/mic.0.043927-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth- and substrate-dependent transcription of formate dehydrogenase and hydrogenase coding genes in Syntrophobacter fumaroxidans and Methanospirillum hungatei

Abstract: Transcription of genes coding for formate dehydrogenases (fdh genes) and hydrogenases (hyd genes) in Syntrophobacter fumaroxidans and Methanospirillum hungatei was studied following growth under different conditions. Under all conditions tested, all fdh and hyd genes were transcribed. However, transcription levels of the individual genes varied depending on the substrate and growth conditions. Our results strongly suggest that in syntrophically grown S. fumaroxidans cells, the [FeFe]-hydrogenase (encoded by Sf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
83
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 33 publications
0
83
1
Order By: Relevance
“…Diffusion kinetics based on Fick's law showed that interspecies formate transfer could sustain a 100-fold higher conversion rate than interspecies hydrogen transfer (7,8). Indeed, several studies have indicated the importance of formate as an electron shuttle in propionate-and butyrate-oxidizing syntrophs (3,(5)(6)(7)(8)(9)(10)(11). However, to our knowledge, this is the first description of its involvement in lactate oxidation of syntrophic Desulfovibrio species.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Diffusion kinetics based on Fick's law showed that interspecies formate transfer could sustain a 100-fold higher conversion rate than interspecies hydrogen transfer (7,8). Indeed, several studies have indicated the importance of formate as an electron shuttle in propionate-and butyrate-oxidizing syntrophs (3,(5)(6)(7)(8)(9)(10)(11). However, to our knowledge, this is the first description of its involvement in lactate oxidation of syntrophic Desulfovibrio species.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, single reports suggest the involvement of cysteine or exogenous carriers such as humic substances (2) as well as the existence of a direct electron transfer via electrically conductive pili called nanowires (4). Exclusive use of hydrogen as an electron carrier has been proven for several syntrophs, while a simultaneous formate/H 2 electron shuttle was proposed to be operative in propionate-and butyrate-degrading cocultures on the basis of early physiological experiments (2,(5)(6)(7)(8)(9) and later confirmed by biochemical and genetic studies (10,11). Indeed, the midpoint redox potentials (E°=) of the redox couples H 2 -H ϩ and formate-CO 2 are similar (Ϫ414 mV and Ϫ432 mV, respectively) (12), but hydrogen and formate have different chemical and physical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The possible role of the Syntrophobacter species is to metabolize propionate to acetate with transfer of reducing equivalents to methanogens (Sieber et al, 2012). Gene expression studies (Worm et al, 2011) and genome analysis (Sieber et al, 2012) have provided strong evidence that the transfer of reducing equivalents between Syntrophobacter species and methanogens proceeds via H 2 and formate. Therefore, Syntrophobacter species are not expected to participate in DIET.…”
Section: Taxonomic Assignment Of 454-sequence Readsmentioning
confidence: 99%
“…Hydrogen and formate are considered to be the primary shuttle compounds for interspecies electron transfer in methanogenic consortia (1)(2)(3). Exclusive use of H 2 as an electron carrier has been proven for several syntrophs, while a combined formate/H 2 electron shuttling has been confirmed in propionate-and butyrate-degrading cocultures (2,(4)(5)(6)(7)(8)(9)(10). Since syntrophic communities exist in conditions close to thermodynamic equilibrium and metabolite exchange is considered to occur primarily via diffusion (1)(2)(3)(4)11), intermicrobial distances influence the efficiency of interspecies transfer (especially for H 2 ), which affects the growth and biodegradation rates of these consortia (2,6,(11)(12)(13).…”
mentioning
confidence: 99%